2009
DOI: 10.1097/opx.0b013e3181a59d78
|View full text |Cite
|
Sign up to set email alerts
|

Binocular Adaptation to +2 D Lenses in Myopic and Emmetropic Children

Abstract: Myopic children demonstrate reduced magnitude and completeness of vergence adaptation to +2 D lenses. The magnitude of vergence adaptation varied with AC/A in both refractive groups; however, the presence of myopia differentiated the amount of adaptation for all AC/A ratios. Conversely, the degree of completeness appears to be primarily associated with the type of refractive error.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 59 publications
4
19
1
Order By: Relevance
“…In emmetropic adults, emmetropic children, and myopic children, monocular conditions either resulted in no significant change in accommodative lag or in a slight increase in accommodative lag of up to 0.25 D compared to binocular viewing conditions (Seidel, Gray, & Heron, 2005; Sreenivasan et al, 2008; Sreenivasan et al, 2009). Although the accommodative testing conditions in CLEERE may have slightly increased the amount of accommodative lag, this should only have enhanced our ability to detect a relationship between lag and the progression of myopia.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In emmetropic adults, emmetropic children, and myopic children, monocular conditions either resulted in no significant change in accommodative lag or in a slight increase in accommodative lag of up to 0.25 D compared to binocular viewing conditions (Seidel, Gray, & Heron, 2005; Sreenivasan et al, 2008; Sreenivasan et al, 2009). Although the accommodative testing conditions in CLEERE may have slightly increased the amount of accommodative lag, this should only have enhanced our ability to detect a relationship between lag and the progression of myopia.…”
Section: Discussionmentioning
confidence: 90%
“…Previous research indicates that extended near work would, at most, slightly reduce the amount of accommodative lag, making it unlikely that temporal aspects of accommodative lag influenced the outcome of this study. Studies have reported either no change in accommodative lag after 30 minutes of reading in adults (Shapiro, Kelly, & Howland, 2005) or a slight decrease in accommodative lag of about 0.25 D after 20 minutes of watching cartoons in myopic children (Sreenivasan, Irving, & Bobier, 2009) and emmetropic adults (Sreenivasan, Irving, & Bobier, 2008). Similarly, more cognitively intense near activities would, at most, be expected to slightly reduce the amount of accommodative lag measured compared to the task of keeping letters clear used in the present study (Kruger, 1980; Winn, Gilmartin, Mortimer, & Edwards, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated reduced accommodative gains in infants and young children when viewing stimuli under monocular versus binocular conditions. 27 However, the increase in accommodative response from monocular to binocular viewing becomes quite small (approximately 0.25D) by school age 28, 29 into adulthood. 30 Given this evidence, it is possible that the lower accommodative amplitudes observed in the preschool aged subjects may be partially attributed to the monocular testing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 At the same time, the near phoria was usually shifted in the exophoric direction and was out of the normal range. A recent report by Sreenivasan et al 45 studied the effect of binocular adaptation to +2 D near-additions on response AC/A ratios of myopic and emmetropic children. Based on their results, they suggested that the +2 D near-additions would reduce both lag of accommodation and esophoria, and therefore may be beneficial for myopic children with near esophoria.…”
Section: Discussionmentioning
confidence: 99%